Coincidental detection of polymicrobial growth in the environment of an outpatient department of ophthalmology - Nishant, Prateek; Kumar, Roshan; Sinha, Sony (Bangladesh Journal of Infectious Diseases, 2025)
Abstract Not Available Bangladesh Journal of Infectious Diseases, December 2024;11(2):228-229